Evaluating an In-School Drug Prevention Program for At-Risk Youth - DeWit, David J.; Steep, Barbara; Silverman, Gloria; Stevens-Lavigne, Andrea; Ellis, Kathy; Smythe, Cindy; Rye, Barbara J.; Braun, Kathy; Wood, Eileen (Alberta Journal of Educational Research, 2000)
This study assessed an in-school program aimed at preventing or reducing drug use and other deviant behavior in a sample of 167 at-risk youth in their transition years. Over 10 weeks, 17 one-hour sessions were offered to youth who were identified using a self-report questionnaire (at 9 schools with 12 control sites in Ontario, Canada). Repeated measures analysis of covariance was used to assess program impact at posttest and six-month followup. Program participants, compared with the control group, reported less frequent drinking,